Banyumas People’s Characteristics Symbolically Reflected on Calung Banyumasan Performance - Suharto, S. (Harmonia: Journal of Arts Research and Education, 2018)
This research aims at examining how Banyumas people’s characteristics are symbolically expressed in Calung Banyumasan performance. This qualitative research employs a hermeneutic approach to examine any symbolic meanings in calung performance. The data are collected by literary study, document study, observation and interview, which are then analyzed using content analysis and interactive analysis of Miles and Huberman. The research results show that some song lyrics identify Banyumas people’s images and characteristics such as equality and honesty (cablaka) just like the ngoko level language they use. The performance consists of opening, Lenggeran, Badhudan, and Baladewan acts in the process of illustrating the character of Banyumas people who love jokes and crowd. Some aspects arising in performance reflect Banyumas people as an egalitarian, straightforward, like-to-gather, and syncretic society.